Penerapan CSR pada Presepsi Mahasiswa Sebagai Pendukung CSR (CSR SUPPORT) di Seluruh PTS di Bandar Lampung - Muprihan Thaib; Ronny Nazar; Dedi Putra (Jurnal Akuntansi dan Keuangan, 2017)
CSR is a social activities been held by the as a form of the responsibility of the company for the society, and environment. CSR refer to all ties what happened between a company with all stakeholders. Students as a community educated, have an important role to play in a community social even them in gave a more objective and intact about how an entity run correctly and without intersects with social norms.Student predicted as a CSR support in giving hope to confidence in a person in support of whether or not certain a CSR in an entity. Alignment between hope students as a supporter of csr with the activities of CSR who was executed by the company would affect CSR company activities. Dimensions law, economic and ethical be hopeless area for a supporter of csr that the company being able to support development of the dimensions so that it becomes independent variable while support csr become the dependent variable for in this research. A method of this research use the model equation structural ( structural equation unified / SEM ) by using path analysis with smart software pls 2.0 .M3 .